Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
The Chile-2015 (Illapel) Earthquake and Tsunami 2017
DOI: 10.1007/978-3-319-57822-4_1
|View full text |Cite
|
Sign up to set email alerts
|

A Review of Source Models of the 2015 Illapel, Chile Earthquake and Insights from Tsunami Data

Abstract: The 16 September 2015 Illapel, Chile, earthquake has been studied by many researchers from various aspects. This paper reviews studies on the source model of the earthquake and examines tsunami data. The Illapel earthquake occurred in the source region of previous earthquakes in 1943 and 1880. The earthquake source was studied by using various geophysical data, such as near-field seismograms, teleseismic waveform and backprojection, GPS and InSAR data, and tsunami waveforms. Most seismogram analyses show the d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 36 publications
1
8
0
Order By: Relevance
“…The 2015 Illapel earthquake struck the northern part of the 1730 event, where two major earthquakes (1943 and 1880) occurred in the same region (Figure 1; Beck et al, 1998). The slip region of the 2015 Illapel earthquake agrees well with the possible rupture zone proposed by Kelleher (1972) and Beck et al (1998), and it is identified as a rerupture of the 1943 earthquake (Satake & Heidarzadeh, 2017). The last major earthquake occurred on 15 October 1997 at a depth of 68 km in the Punitaqui region, and located in the northeastern segment of the 1939 event ( Figure 1).…”
Section: Historical Earthquakes and Earthquakes Cyclesupporting
confidence: 71%
“…The 2015 Illapel earthquake struck the northern part of the 1730 event, where two major earthquakes (1943 and 1880) occurred in the same region (Figure 1; Beck et al, 1998). The slip region of the 2015 Illapel earthquake agrees well with the possible rupture zone proposed by Kelleher (1972) and Beck et al (1998), and it is identified as a rerupture of the 1943 earthquake (Satake & Heidarzadeh, 2017). The last major earthquake occurred on 15 October 1997 at a depth of 68 km in the Punitaqui region, and located in the northeastern segment of the 1939 event ( Figure 1).…”
Section: Historical Earthquakes and Earthquakes Cyclesupporting
confidence: 71%
“…The megathrust event ruptured an about 200 km long stretch along the Central Chilean subduction zonewhere the Nazca Plate subducts beneath the South American Plate(Ye et al, 2017). Previous larger earthquakes occured in this region in 1943 and 1880 (e.g Satake and Heidarzadeh, 2017;Ye et al, 2017)…”
mentioning
confidence: 87%
“….The Chilean subduction zone is prone to large megathrust events with the Illapel event being the third tsunamigenic earthquake with a magnitude greater than 8 in Northern and Central Chile in this decade (first event was the 2010 Mw 8.8 Maule event, second was the 2014 Mw 8.1 Iquique event). The largest slip (between 5 and 16 m) is located about 70 km to the NW of the epicentre and with the shallow part of the slip seeming to extend to the trench axis(Satake and Heidarzadeh, 2017). The main shock triggered various aftershocks (1388 events in the ISC Bulletin between 33 • S to 29 • S and 73 • W to 71…”
mentioning
confidence: 99%
“…The kinematic rupture process of the 2015 Illapel earthquake has been studied by many groups; some use a combination of teleseismic waveform and geodetic data (i.e., Barnhart et al., 2016; Carrasco et al., 2019; Grandin et al., 2016; Klein et al., 2017; Lange et al., 2016; Meng et al., 2018; Okuwaki et al., 2016; Williamson et al., 2017; Zhang et al., 2016) and the others include tsunami information (i.e., An et al., 2017; Li et al., 2016; Satake & Heidarzadeh, 2017; Williamson et al., 2017). However, the strong motion data of the National Seismological Center and the continuous recording of 1‐s sampling of GNSS data (Baez et al., 2018; Leyton et al., 2018a) have not yet been sufficiently explored.…”
Section: Introductionmentioning
confidence: 99%